Drug Induced Sialorrhea and Microfluidic-Chip-Electrophoretic Analysis of Engorged Adult Female Tick Saliva of Haemaphysalis longicornis (Acari: Ixodidae) - Mohammad Saiful Islam; Myung Jo You (Journal of Arthropod-Borne Diseases, 2017)
Background: The aim of the present study was to induce salivation in Haemaphysalis longicornis to increase saliva production and to characterize the collection of proteins present in the collected saliva using on-chip-electrophoresis. Methods: Saliva of adult female engorged H. longicornis was collected by treatment with 0.2% dopamine hydrochloride. All protein samples were characterized by SDS-PAGE electrophoresis using a microfluidic High Sensitivity Protein Assay 250 kit by 2100 Bioanalyzer (Agilent Technologies, USA) under non-reducing conditions. Results: The average salivary protein concentration was 0.169 µg/µl/tick and saliva secretion decreased with increased time of tick detachment from the host. Saliva secretion volume increased to 3.56 µl in the group of ticks with a body weight between 301–350 mg as compared to higher and lower body weight groups. On-chip-electrophoresis results show 13 distinct bands ranging from 9.9 to 294 kDa. Conclusion: Based on molecular weight, the putative salivary proteins are comprised of proline-rich proteins, triabin, apyrase members of the 12-kDa protein family, platelet inhibitors and anti-inflammatory proteins as tick saliva contains anti-inflammatory components.